Pengaruh Konsentrasi Ekstrak Buah Belimbing Wuluh (Averrhoa bilimbi) sebagai Koagulan Alami terhadap Karakteristik Karet Klon PB 260 - Achmad, Feerzet; Amelia, Devita; Pratiwi, Ayu; Wahyu Saputri, Laila; Deviany; Yuniarti, Reni; Suhartono; Suharto (Talenta Publisher (Universitas Sumatera Utara), 2022)
Averrhoa bilimbi is a plant rich in benefits, one of which as natural coagulant. The aim of this research is to increase the potential of Averrhoa bilimbi as an environmentally friendly natural coagulant for the coagulation of rubber clone PB 260. The concentrations of Averrhoa bilimbi used were 45%, 55%, 65%, 75% and 85%. The characteristics of the rubber tested were dry rubber content (DRC), initial plasticity (Po) and Plasticity Retention Index (PRI). Based on the results of this study, the optimum concentration of Averrhoa bilimbi is 85% for latex coagulation time of 11 minutes with 33% DRC, 41% Po and 97% PRI. The highest the concentration of Averrhoa bilimbi used, the faster the coagulation process occurred. 2% formic acid was used as a chemical coagulant for comparison. From the results of this study, it can be concluded that Averrhoa bilimbi can be used as a natural coagulant producing rubber characteristics equal in quality as the ones using formic acid as a chemical coagulant and meets Indonesian Rubber Standard SNI 06-1903-2000.